Pgrmc1: new roles in the microglial mediation of progesterone-antagonism of estradiol-dependent neurite sprouting and in microglial activation - Bali, Namrata; Morgan, Todd E.; Finch, Caleb E. (Frontiers in Neuroscience, 2013)
Pgrmc1 (progesterone receptor membrane component 1) is a multifunctional 22 kDa protein with heme-binding and P450-activating capacity which was recognized under different names for roles in cell motility during neural development and in cancer, and apoptosis. Pgrmc1 expression in microglia was recently shown by the present authors to mediate estrogen-progesterone interactions during axonal sprouting and to mediate microglial activation itself. We also discuss other functions of Pgramc1 in the nervous system and its possible relationship to the 18 kDa sigma-2 receptor (S2R).